Komposisi Jenis dan Ukuran Lobster (Panulirus sp.) Hasil Tangkapan di Pantai Yeh Gangga Kabupaten Tabanan dan Pantai Canggu Kabupaten Badung Provinsi Bali - Asvin, Muhammad Rizky; Restu, I Wayan; Ekawaty, Rani (Current Trends in Aquatic Science; Vol 2 No 1 (2019), 2019)
Lobster is one of the potential fisheries commodities and an important economic category for export. The research was conducted in December 2018 until January 2019 with objectives to determine the composition and range of sizes of lobster caught by the fishermen and the tools and methods used to catch lobsters on Canggu Beach and Yeh Gangga Beach. The method used for the data collection was survey and interview methods. Sampling was done for 2 months with 1 sampling each month. Samples were taken from the catch of the fishermen. Lobster samples were then identified by type and carapace length measurements, total length, and lobster weight. Data obtained from lobster composition were analyzed descriptively and displayed in graphs and tables, while analysis of lobster fishing methods was carried out descriptively by collecting data on types, quantities, and methods of operation of fishing gear. R esults showed the composition of the types of lobsters caught on Canggu Beach were Panulirus penicillatus, P. homarus, P. versicolor, P. longipes, and P. ornatus. The catch in Canggu Beach was dominated by the type of P. homarus as much as 38% in the first data collection and as much as 39% in the second data collection. The composition of lobster catches on Yeh Gangga Beach, namely P.  penicillatus, P. homarus, P. versicolor, P. longipes, and P. ornatus. The first data collection was dominated by the type of P . homarus as much as 36% and the second data collection was 46%. The caught lobster has an average carapace length below 8 cm and has a weight above the average, which was 200 grams. The type of fishing gear used to catch lobsters was a passive catch in the form of traps and nets.